Efficient and reductive removal of bromate using a novel and stable nanoscale zero-valent iron embedded in N-doped carbon derived from metal-organic frameworks. (November 2022) - Li, Long; He, Yuhao; Fu, Heyun; Qu, Xiaolei; Xu, Zhaoyi
Abstract: Nanoscale zero-valent iron (nZVI) has drawn great interest in the remediation of contaminated waters. In this study, we prepared a novel and stable nZVI embedded in N-doped carbon matrix (nZVI@MOF-CN) using a facile direct carbonization method, in which an iron-containing metal-organic framework (MOF) served as both the iron and carbon sources, and melamine as the nitrogen source. The nZVI@MOF-CN composites were used in the removal of bromate in water, which could be effectively reduced by the surface electrons transferred from nZVI to the carbon encapsulation layer due to the Schottky-Mott effect. Doped nitrogen significantly facilitated the reduction of bromate by nZVI, because it enhanced the nZVI dispersion and bromate adsorption, and modulated the carbon matrix conductivity. The bromate reduction activity of nZVI@MOF-CN was more than 50 times higher that of its un-doped counterpart and a commercial nZVI. Moreover, owing to the protection of carbon encapsulation layer, nZVI@MOF-CN exhibited good stability and reusability. The leached concentration of iron ions of nZVI@MOF-CN was less than 5% of the commercial nZVI under the same reaction conditions. Commercial nZVI almost completely lost its bromate reduction activity after use (3% reduction efficiency in the examined time frame), while nZVI@MOF-CN maintained a reduction efficiency of 61%. The nZVI@MOF-CN could be effectively regenerated by hydrogenation reduction. After five reaction-regeneration cycles, nZVI@MOF-CN still achieved a bromate reduction efficiency of approximately 80%. These results suggest that MOF-derived nZVI materials are highly reactive and stable for the reductive removal of pollutants in water. Graphical abstract: Image 1 Highlights: A nZVI embedded in N-doped carbon (nZVI@MOF-CN) was prepared by MOF carbonization. The nZVI@MOF-CN can effectively reduce bromate due to the Schottky-Mott effect. Doped nitrogen played a critical role in the reduction of bromate by nZVI@MOF-CN. Carbon encapsulation layer rendered nZVI@MOF-CN enhanced stability and reusability.